Vulnerability and Survival Strategy by Food Street Vendors (PKL): Study Cases in Triangle Gold of DKI Jakarta - Rachmawan, Dicky; Fathy, Rusydan; Luthfi, Muhammad (JSW (Jurnal Sosiologi Walisongo), 2021)
City bias development especially DKI Jakarta effects on the high rate of urbanization, where abundant workforce from rural areas work as an informal economy workers as street vendor (PKL). Eviction for PKL still happens in recent time although ineffective. The qualitative method is used with study case empowered by life history for revealing the vulnerability and survival strategy of PKL. Result shows that earn income same as minimum wage regional in Jakarta by PKL is not a problem, there are two factors as PKLâ€™s vulnerability which come from the external aspect, that are eviction and number of the costumer. Adaptation for following the change of rule and bridging with stakeholders are the main strategies by PKL to survive, biside same of identity and norm of PKL have function as cohesivity adhesive to face life. Finally, risignation value to God and effort for development are determinant aspect which differs between PKL who have more or less revenueÂ Pembangunan bias perkotaan khususnya di DKI Jakarta berdampak pada terjadinya tingginya urbanisasi, dimana kelebihan tenaga kerja desa bekerja sebagai pekerja sektor informal seperti menjadi pedagang kaki lima (PKL). Penggusuran masih terjadi sampai saat ini khususnya bagi para PKL meskipun tidak efektif. Metode kualitatif dengan studi kasus digunakan yang diperkuat dengan life history untuk mengungkapkan kerenantan dan strategi bertahan para rumah tangga PKL. Hasilnya ternyata mendapatkan penghasilan setara UMR di Jakarta bagi PKL bukanlah sebuah permasalahan, terdapat dua faktor kerentanan PKL yang cenderung berasal dari aspek eksternal yaitu penggusuran dan jumlah konsumen. Adaptasi untuk mengikuti perubahan aturan dan bridging dengan para pihak adalah strategi utama agar PKL dapat bertahan, disamping satu identitas dan norma-norma PKL sebagai perekat kebersamaan menghadapi kehidupan. Terakhir nilai-nilai kepasrahan kepada Tuhan dan semangat untuk terus maju adalah aspek yang menentukan perbedaan sikap antara mereka yang memiliki pendapatan besar dan kecil.